Identification of canonical pyroptosis-related genes, associated regulation axis, and related traditional Chinese medicine in spinal cord injury - Shan, Wenshan; Li, Shuang; Yin, Zongsheng (Frontiers in Aging Neuroscience, 2023)
Neuroinflammation plays an important role in spinal cord injury (SCI), and pyroptosis is inflammatory-related programmed cell death. Although neuroinflammation induced by pyroptosis has been reported in SCI, there is a lack of systematic research on SCI pyroptosis and its regulation mechanism. The purpose of this study was to systematically analyze the expression of pyroptosis-related genes (PRGs) in different SCI models and associated regulation axis by bioinformatics methods. We downloaded raw counts data of seven high-throughput sequencings and two microarray datasets from the GEO database, classified by species (rat and mouse) and SCI modes (moderate contusive model, aneurysm clip impact-compression model, and hemisection model), including mRNAs, miRNAs, lncRNAs, and circRNAs, basically covering the acute, subacute and chronic stages of SCI. We performed differential analysis by R (DEseq2) or GEO2R and found that the AIM2/NLRC4/NLRP3 inflammasome-related genes, GSDMD, IL1B, and IL18, were highly expressed in SCI. Based on the canonical NLRP3 inflammasome-mediated pyroptosis-related genes (NLRP3/PRGs), we constructed transcription factors (TFs)–NLRP3/PRGs, miRNAs- Nlrp3/PRGs and lncRNAs/circRNAs/mRNAs–miRNA- Nlrp3/PRGs (ceRNA) networks. In addition, we also predicted Traditional Chinese medicine (TCM) and small, drug-like molecules with NLRP3/PRGs as potential targets. Finally, 39 up-regulated TFs were identified, which may regulate at least two of NLRP3/PRGs. A total of 7 down-regulated miRNAs were identified which could regulate Nlrp3/PRGs. ceRNA networks were constructed including 23 lncRNAs, 3 cicrRNAs, 6 mRNAs, and 44 miRNAs. A total of 24 herbs were identified which may with two NLRP3/PRGs as potential targets. It is expected to provide new ideas and therapeutic targets for the treatment of SCI.